Analisis Sistem Informasi Akuntansi Pengadaan Barang di Kantor BPJS Ketenagakerjaan Cabang Manado - Syaefudin, Fanesa Isalia Minanda; Hermansyah, Sherryn Veronica; Pangemanan, Shane Anneke; Siahaan, Belthasar Trito (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The principle that must be adhered to in organizing procurement is that it is oriented towards quality and correct specifications. In carrying out the goods procurement process, there is a flow of procedures and rules for procurement of goods that must be in place in the procurement process starting from procurement, documents, making reports and arriving at storage in the warehouse. The aim of this research is to analyze the Goods Procurement Accounting System implemented by the Manado Branch of the BPJS Employment Office. Using a type of qualitative research, the data analysis used is descriptive. Data collection techniques are through observation, interviews and documentation. The results of this research indicate that the Goods Procurement Accounting System implemented is running in accordance with the provisions implemented by the Head Office. The author recommends that for Procurement of Goods at the Manado Branch BPJS Employment Office create a flowchart to make it easier to carry out a process in a company program that is carried out for smooth work operations.